THE ROLE OF MINIMALLY INVASIVE TECHNOLOGIES IN THE COMPLEX TREATMENT OF PERITONITIS - Berdiev Ergash Abdullaevich; Atakov Sarvar Sultanbaevich; Mukhidinov Abdulla Umidilloevich (Web of Journals Publishing, 2024)
The article presents the experience of complex treatment of children with peritoneal adhesions. During the period of 2010-2023, 96 patients with obvious pain syndrome on the background of peritonitis were operated on. Of these, 48 had obvious peritoneal adhesions, and in order to facilitate a complete videoendolaparoscopic adhesiolysis surgery, a centrally created fibrinolytic mixture was injected into the abdominal cavity before surgery; (composition of fibrinolytic mixture: heparin 10000 ED+ fibrinolysin 20000 ED+ hydrocortisone 125mg+ gentamicin 80mg+ novocaine 0.25%-200ml), and schemetreatment procedures were carried out. Complications and their recurrence were not observed after the operation.Endovideolaparoscopic technologiesAll patients who underwent surgery were activated early and had an average of 3.7 days of inpatient treatment.
Keywords: Adhesion disease, children, prevention, videolaparoscopic adheziolysis.